Studies on Coriandrum sativum linn seed of different origin of Bangladesh for its essential oil, fatty oil and micronutrients (Bangladesh Journal of Scientific and Industrial Research, 2014)
Four varieties of Coriandrum sativum Linn seed from different origin of Bangladesh such as Brahmanbaria, Faridpur, Keranigonj, Sirajgonj and one variety of Coriandrum sativum Linn seed powder of widely used brand "Radhuni" was collected from the local market. Comparative study of the collected samples and derived oils for proximate analysis, physico-chemical characteristics, essential oils, fatty oils compositions and micronutrient analysis were performed. In proximate analysis carbohydrate, protein, fiber, fat, ash and energy contents were calculated for the five varieties. The samples were extracted by hydro-distillation and it was found that the coriander seed contained 0.15% to 0.25% of essential oils. The chemical constituents of the derived essential oils were determined by FTIR and GC-MS. The fatty oils from the sample were extracted by successive solvent extraction method and the physico-chemical characteristics were determined by usual standard procedure. The chemical compounds of the fatty oil were identified and quantified by FTIR, GC-MS and the micronutrient analysis was conducted using ED-XRF analyzer. The major elements were found to be K, Ca, Cl and percent yield were in the range of 41.74-45.77, 38.77-44.24, 4.30-6.19 respectively. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18272 Bangladesh J. Sci. Ind. Res. 48(4), 221-228, 2013